DEVELOPMENT OF A PROJECT-BASED ARTS LEARNING MANAGEMENT MODEL TO FOSTER CREATIVE AND MEANINGFUL LEARNING IN ELEMENTARY SCHOOLS - Indani Damayanti (Universitas Majalengka, 2025)
Arts education in elementary schools plays a strategic role in fostering students' creativity, critical thinking, collaboration, and aesthetic appreciation. However, its implementation continues to face several challenges, including fragmented instructional planning, unsystematic learning management, and the limited availability of management models that effectively support project-based arts learning. This study aimed to develop a Project-Based Arts Learning Management Model that is valid, practical, and effective in promoting creative and meaningful learning in elementary schools. The study employed a Research and Development (R&D) approach using the Plomp development model, which consists of three phases: preliminary research, prototyping phase, and assessment phase. During the preliminary research phase, a needs analysis was conducted through classroom observations, semi-structured interviews, and document analysis. The prototyping phase involved designing the model, validating it through experts in educational management, arts education, and elementary education, and revising the prototype based on expert feedback. Subsequently, the assessment phase was carried out through a limited field trial to evaluate the model's validity, practicality, and effectiveness. Data were collected using validation sheets, questionnaires, classroom observations, and documentation, and were analyzed using descriptive quantitative and qualitative techniques. The findings indicate that the developed model satisfies the criteria of validity, practicality, and effectiveness in improving the quality of arts learning management and enhancing students' engagement throughout the learning process. The proposed model provides a systematic and innovative framework for elementary school teachers to manage arts learning while promoting meaningful learning experiences and fostering students' creativity.